Proceedings of the 19th Australasian Conference on Computer-Human Interaction: Entertaining User Interfaces 2007
DOI: 10.1145/1324892.1324932
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of eye-gaze interaction methods for security enhanced PIN-entry

Abstract: Personal identification numbers (PINs) are one of the most common ways of electronic authentication these days and used in a wide variety of applications, especially in ATMs (cash machines). A non-marginal amount of tricks are used by criminals to spy on these numbers to gain access to the owners' valuables. Simply looking over the victims' shoulders to get in possession of their PINs is a common one. This effortless but effective trick is known as shoulder surfing. Thus, a less observable PIN entry method is … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
61
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 87 publications
(70 citation statements)
references
References 12 publications
3
61
0
Order By: Relevance
“…For example, researchers in [12,4] attempted to use similar gazing-based technique as in [7] to enter sensitive input from an on-screen keyboard. The evaluation of EyePIN in [4] showed promise, but it also seems to have revealed some usability problems when users needed to remember and understand the new alphabet gestures in order to use them. Also, additional hardware costs for eye tracking equipment are needed for this type of approaches.…”
Section: Related Workmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, researchers in [12,4] attempted to use similar gazing-based technique as in [7] to enter sensitive input from an on-screen keyboard. The evaluation of EyePIN in [4] showed promise, but it also seems to have revealed some usability problems when users needed to remember and understand the new alphabet gestures in order to use them. Also, additional hardware costs for eye tracking equipment are needed for this type of approaches.…”
Section: Related Workmentioning
confidence: 99%
“…For example: the sequence Pen-up, (1,2), (1,3), (1,4), Pen-up defines a stroke: (1,2), (1,3), (1,4). The length of a stroke is the number of coordinate pairs it contains.…”
Section: Draw a Secret Schemementioning
confidence: 99%
“…Luca et al [15] evaluated different authentication techniques for ATM usage. During the experimentations they found that many users tend to support their memory for their 4-digit-PINs by incorporating the layout of the digits on the number pad and the shape resulting from these spatial relations.…”
Section: Related Workmentioning
confidence: 99%
“…The currently adopted approaches consider eye gaze as an alternative way to input user-specific PIN numbers or passwords; see [Kumar et al 2007] for a recent review of such methods. In these systems, the user may input the pass-phrase by, for instance, gazetyping the password [Kumar et al 2007], using graphical passwords such as human faces [Passfaces ], or using gaze gestures similar to mouse gestures in web browsers [Luca et al 2007]. In such systems, it is important to design the user interface (presenting the keypad or visual tokens; providing user feedback) to find acceptable trade-off between security and usability -too complicated cognitive task becomes easily distracting.…”
Section: Related Workmentioning
confidence: 99%